Légitimation et pérennisation des élites politiques dans la subjectivation de la démocratisation en Province Orientale démembrée/ République Démocratique du Congo - Ke’ Bongo Bongo, Matthieu Mamiki (IJRDO - Journal of Social Science and Humanities Research, 2018)
Democratization has reopened in the Democratic Republic of  Congo with a great hope of political modernization and the concern for socio-economic development of all. This last factor that eventually redirects all political practices at the expense of the basis of democracy. Therefore it develops various mode of ownership of democracy among these modes is the transhumance. This subjective then democratization to the point that the populations of  downstairs(one’s rocker) and elites at the top swear by the power to emerge, to legitimize itself and to outlive socially and economically.This article based on the institutionalism and the theory of the "three I" shows that, since the democratization, it developed in Eastern Province two types of socio-political actors: the people of downstairs(peasant and public servant) which, once access power cling and are co-opted by the old elite long in power, people at the top. The two, using transhumance, live only of power and the power. The first know so inclusive legitimacy as the second subject to exclusive legitimacy.These justifications though reduced helped these two actors to perpetuate themselves in power to the point that they are the ones who are institutionalized instead of democratic institutions (parties and associations). There is no democratic ideological development but a mystification of the elites. Parties, associations, or any organized group remained always weak and poorly organized while these elites become strong socially, economically and even politically. This are the ones who ultimately shape democracy on their own. No longer are the parties who make competition on basis of their ideologies, but of individuals based on their resources acquired by their access to the reins of power.